Eksplorasi Dimensi Efikasi Diri Guru Fisika di Kalimantan Barat - Sari, Ira Nofita; Nurussaniah, Nurussaniah (Universitas Hamzanwadi, 2023)
Physics teachers need to pay more attention to each student's unique way of thinking, strive to recognize and correct misunderstandings, and apply cognitive learning methods such as assimilation and accommodation. The use of cognitive dissonance can be used as a tool to change students' way of thinking. Additionally, it is important to simplify experiments and provide practical exercises that can deepen students' understanding. Teachers must also be able to relate lesson material to real life and understand the role of emotions in the teaching and learning process. Therefore, it is necessary to have teacher self-confidence through self-efficacy. This study aims to provide a comprehensive understanding of the condition of educators' self-efficacy in West Kalimantan and its impact on learning. This research is a descriptive research. The population of this research is all physics teachers in West Kalimantan. The sample was selected using probability sampling technique. The number of samples in this study were 100 physics teachers from 13 cities/districts in West Kalimantan. Data collection technique is indirect communication. Data analysis used descriptive statistics, followed by a description of the physics teacher's level of self-efficacy. Based on the research results it was concluded that the average self-efficacy level of physics teachers in West Kalimantan was quite high. The factors measured, namely the efficacy in learning strategies, classroom management, and student involvement all show a good level of self-efficacy. Physics teachers in West Kalimantan demonstrated high efficacy in developing learning strategies and managing classrooms, and had sufficient confidence in engaging students in the learning process.